IMPLEMENTASI SISTEM INFORMASI BERBASIS WEB DALAM PELACAKAN DAN ENGAGEMENT DATA ALUMNI (STUDI KASUS: SMA NEGERI 1 ANJIR PASAR) - Pratiwi, Evi Lestari; Aulia Hasanah , Dini; Misriana , Risni; Noor Pratama, Ramadhani (P3M Politeknik Negeri Banjarmasin, 2025)
This research implements a web-based information system for alumni data tracking and engagement at SMA Negeri 1 Anjir Pasar. The main problem addressed is the inefficiency and data vulnerability of the previously existing manual alumni data collection system. Utilizing a Prototype model approach, this system was designed and built to provide functionalities for alumni data management, activity news dissemination, and job vacancy information display. Black Box testing results indicate that the system functions optimally and meets the defined functional requirements. This implementation successfully enhances administrative efficiency in digital data management, facilitates information access for alumni, and strengthens communication and networking between the school and its graduates. The contribution of this research lies in providing an effective digital solution for alumni management, supporting the improvement of the educational institution's image and services